Application of the optimizing health literacy and access (Ophelia) process in partnership with a refugee community in Australia: Study protocol - Jawahar, Zaman; Elmer, Shandell; Hawkins, Melanie; Osborne, Richard H. (Frontiers in Public Health, 2023)
Refugees experience health inequities resulting from multiple barriers and difficulties in accessing and engaging with services. A health literacy development approach can be used to understand health literacy strengths, needs, and preferences to build equitable access to services and information. This protocol details an adaptation of the Ophelia (Optimising Health Literacy and Access) process to ensure authentic engagement of all stakeholders to generate culturally appropriate, needed, wanted and implementable multisectoral solutions among a former refugee community in Melbourne, Australia. The Health Literacy Questionnaire (HLQ), a quantitative survey tool which has been widely applied across the world in different population groups including refugees, is generally used within the needs assessment stage of the Ophelia process. However, this protocol outlines a different approach that is tailored to the local context and the literacy, as well as health literacy needs of former refugees. This project will engage a refugee settlement agency and a former refugee community (Karen people origin from the country of Myanmar also formerly knowns as Burma) in codesign from inception. A needs assessment will identify health literacy strengths, needs, and preferences, basic demographic data and service engagement of the Karen community. This community will be engaged and interviewed using a semi-structured interview based on the Conversational Health Literacy and Assessment Tool (CHAT) covering supportive professional and personal relationships, health behaviours, access to health information use of health services, and health promotion barriers and support. Using the needs assessment data, vignettes that portray typical individuals from the target community will be developed. Stakeholders will be invited to participate in ideas generation and prioritisation workshops for in-depth discussion on what works well and not well for the community. Contextually and culturally appropriate and meaningful action ideas will be co-designed to respond to identified health literacy strengths, needs, and preferences of the community.